Vertical Distribution of the Aerosol Mass Concentration in East Asia Using CALIPSO Data - Sihan Li; Siqi Qi; Xiaojun Ma (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2025)
In this work, a set of retrieval methods for evaluating the aerosol mass concentration suitable for high-pollution areas is used to study the vertical distribution of the $\text{PM}_{2.5}$ mass concentration in different regions of East Asia from 2007 to 2016, high-resolution satellite active remote sensing data. Research has revealed that high-pollution areas in East Asia are located mainly in the Taklamakan Desert, northern India, and northern China, followed by Southeast Asia and southern China. The aerosol thickness in the dust source areas of eastern China is generally 4 km, with an average $\text{PM}_{2.5}$ mass concentration of 60.3 μg · m−1 in the aerosol layer. In densely populated areas, the aerosol thickness is 2 km, with an average $\text{PM}_{2.5}$ mass concentration of 40.9 μg · m−1 in the aerosol layer. Results from this work can be used for further analysis of the aerosol effects on weather and climate in East Asia.